Processioner: Indledning - Jensen, Hans Jørgen Lundager (Religionsvidenskabeligt tidsskrift, 2017)
The introduction to this thematic issue of Religionsvidenskabeligt Tidsskrift provides an overview of contemporary lexical discussions of and explications of processions, a discussion of reasons for a certain tendency to forget about processions and a consideration of processions in relation to basic theories of ritual.